2004
DOI: 10.1902/jop.2004.75.2.249
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of Interleukin‐1β and Prostaglandin E2 on Expression of Receptor Activator of Nuclear Factor‐κB Ligand in Human Periodontal Ligament Cells

Abstract: Human periodontal ligament cells activated with inflammatory factors such as IL-1beta and PGE2 may directly stimulate osteoclastogenesis through RANKL, which is stimulated to express by these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 61 publications
4
66
0
2
Order By: Relevance
“…After utilizing GsMTx4, mechanical stress-induced NF-kB nuclear translocation and osteoclastogenesis-associated genes such as Cox2, RANKL were restrained. In addition to the inhibition of Cox2 and RANKL gene expression, we also found that static mechanical compression promotes the secretion of PGE2, which is consistent with the findings of previous studies 26,27 that claim that PGE2 has a role in osteoclastogensis. 26,27 Furthermore, GsMTx4 can also restrain the upregulation of PGE2.…”
Section: Discussionsupporting
confidence: 92%
“…After utilizing GsMTx4, mechanical stress-induced NF-kB nuclear translocation and osteoclastogenesis-associated genes such as Cox2, RANKL were restrained. In addition to the inhibition of Cox2 and RANKL gene expression, we also found that static mechanical compression promotes the secretion of PGE2, which is consistent with the findings of previous studies 26,27 that claim that PGE2 has a role in osteoclastogensis. 26,27 Furthermore, GsMTx4 can also restrain the upregulation of PGE2.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, there are regulatory interactions mediated by non-T-cell sources (i.e., B and NK cells) (8,23) or different cytokines (i.e., TNF-␣ and IL-1) (2,34,18,38,41,45) that may, at least in part, contribute to the above phenomenon, as it has been shown that B and NK cells can express RANKL and IFN-␥, respectively, associated with bone remodeling (8,23). On the same token, it requires further study to seek whether periodontal resident in tissues or cells can potentially influence RANKL-mediated osteoclastogenesis in vivo (15,32,33,37). Lastly, it is known that IFN-␥ can up-regulate the expression of major histocompatibility complex class II and other accessory molecules on the antigen-presenting cells, leukocytes, and mesenchymal cells, which may further recruit other signaling molecules and/or immune effectors associated with bone remodeling (12,17,31).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have supported the new paradigm of linking adaptive immunity and bone remodeling (termed osteo-immunology) associated with various inflammatory bone disorders (1, 5, 19-20, 25-26, 28-30, 40, 46, 50, 53). More recently, studies have shown that periodontal residen T cells and tissues (i.e., periodontal ligament and fibroblast tissues) can also be induced to express RANKL/OPG under microbe-or microbial product-induced inflammatory conditions in vivo or/and in vitro (15,(32)(33)37), suggesting the broad contributions of cytokine RANKL-RANK/OPG signaling network in periodontal disease.…”
mentioning
confidence: 99%
“…IL-1␤ is a potent stimulator of bone resorption and an inhibitor of bone formation that enhances osteoclast differentiation and acts as a survival factor for mature osteoclasts (26,31,54). It has been shown previously to activate RANKL in PDL cells (40). TNF-␣ promotes the production of RANKL and macrophage colony-stimulating factor by stromal cells and induces osteoclast formation.…”
Section: Vol 76 2008mentioning
confidence: 99%